ESPR uroradiology task force and ESUR paediatric working group: imaging recommendations in paediatric uroradiology, part IV: Minutes of the ESPR uroradiology task force mini-symposium on imaging in childhood renal hypertension and imaging of renal trauma in children. - Riccabona M; Lobo ML; Papadopoulou F; Avni FE; Blickman JG; Dacher JN; Damasio B; Darge K; Ording-Müller LS; Vivier PH; Willi U; Riccabona, Michael; et al. (Pediatric Radiology, 2011)
Two new recommendations of the European Society of Radiology task force and the European Society of Uroradiology workgroup on paediatric uroradiology are presented. One deals with diagnostic imaging in children after trauma to the urinary tract-renal trauma, in particular. The other concerns the evaluation of suspected renal hypertension. Available data in the paediatric literature are either unsatisfactory or controversial for both of these clinical settings. Therefore, the following consensus-based proposals aim at outlining effective imaging algorithms to reduce invasive imaging procedures while optimising diagnostic accuracy. The objective of following a more uniform imaging approach is to facilitate future meta-analysis as well as multicentre and other more evidence-based studies. The practise in paediatric radiology is typically based on local availability and on the limitations of professional expertise and equipment, balanced against the perceived needs of the individual child. Although this is unlikely to change in the near future, it does not release the physicians in charge of diagnostic imaging from their responsibility in choosing and providing state-of-the-art imaging and management protocols that are adapted specifically for use in children.